Elongation factor 2 in cancer: a promising therapeutic target in protein translation - Xuechao Jia; Chuntian Huang; Fangfang Liu; Zigang Dong; Kangdong Liu (Cellular & Molecular Biology Letters, 2024)
Abstract Aberrant elongation of proteins can lead to the activation of oncogenic signaling pathways, resulting in the dysregulation of oncogenic signaling pathways. Eukaryotic elongation factor 2 (eEF2) is an essential regulator of protein synthesis that precisely elongates nascent peptides in the protein elongation process. Although studies have linked aberrant eEF2 expression to various cancers, research has primarily focused on its structure, highlighting a need for deeper exploration into its molecular functions. In this review, recent advancements in the structure, guanosine triphosphatase (GTPase) activity, posttranslational modifications, regulatory factors, and inhibitors of eEF2 are summarized. These findings provide a comprehensive cognition on the critical role of eEF2 and its potential as a therapeutic target in cancer. Furthermore, this review highlights important unanswered questions that warrant investigation in future research. Graphical Abstract